DHA and EPA Alleviate Epileptic Depression in PTZ-Treated Young Mice Model by Inhibiting Neuroinflammation through Regulating Microglial M2 Polarization and Improving Mitochondrial Metabolism - Yueqi Yang; Lu Chen; Ning Zhang; Yingcai Zhao; Hongxia Che; Yuming Wang; Tiantian Zhang; Min Wen (MDPI AG, 2023)
Depression is the most common complication of childhood epilepsy, leading to a poor prognosis for seizure control and poor quality of life. However, the molecular mechanisms underlying epileptic depression have not been completely elucidated. Increasing evidence suggests that oxidative stress and neuroinflammation are major contributors to depression. The positive effects of dietary supplementation with docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) on depression have been previously reported. However, knowledge regarding the effects of EPA and DHA in managing depressive symptoms in pediatric patients with epilepsy is limited. Therefore, this study aims to investigate the effects of EPA and DHA on epileptic depression in a pentylenetetrazole (PTZ)-treated young mouse model. Three-week-old mice were fed a DHA- or EPA-enriched diet for 21 days and treated with PTZ (35 mg/kg, i.p.) every other day for a total of 10 times. EPA was more effective than DHA at alleviating PTZ-induced depressive symptoms. Pathological results revealed that DHA and EPA significantly improved neuronal degeneration in the hippocampus. Analysis of the mechanism revealed that DHA and EPA mitigated PTZ-induced myelin damage by increasing the protein levels of CNPase, Olig2, and MBP. Furthermore, both DHA and EPA reduced neuroinflammation by promoting microglial M2 polarization and suppressing the LCN2-NLRP3 inflammasome pathway. Notably, EPA polarized microglia towards the M2 phenotype. In addition, DHA and EPA decreased oxidative stress by inhibiting NOX2 and enhancing mitochondrial metabolism through the increased expression of mitochondrial respiratory chain complex I-V proteins. These findings suggest that DHA and EPA can be used as effective interventions to improve depression in children with epilepsy, with EPA being a particularly favorable option.